Educational innovation: Integration of face-to-face and online in teaching and learning in higher education - Nogueira, Teresinha de Jesus Araújo Magalhães; Melo , Lívia Veleda Sousa e; Ferreira , Marcello; Leite , Letícia Lopes; Barrera , Débora Furtado (Seven Editora, 2023)
This study aims to analyze the results of the Learning Program for the 3rd Millennium (A3M), developed by the University of Brasília (UnB) to identify, promote and disseminate innovative educational actions in the institution and its integration between face-to-face and online. Part of the problem: what is the potential for educational innovation in the projects identified and developed in the A3M Program and the possibilities for the convergence of modalities? The result points to the use of active methodologies, the consideration of new educational spaces, the use of digital information and communication technologies (DICT) in didactic strategies, the understanding of teaching as pedagogical mediation and of the student as an active subject of their learning. Educational practices suggest possibilities for convergence of modalities and the use of blended learning. DOI:https://doi.org/10.56238/sevened2023.006-074